Ecological mismatches are moderated by local conditions for two populations of a long‐distance migratory bird. Issue 1 (7th June 2016) - Senner, Nathan R.; Stager, Maria; Sandercock, Brett K.
Abstract : Ecological mismatches between reproductive events and seasonal resource peaks are frequently proposed to be a key driver of population dynamics resulting from global climate change. Many local populations are experiencing reduced reproductive success as a consequence of mismatches, but few mismatches have led to species‐level population declines. To better understand this apparent paradox, we investigated the breeding phenology and chick survival of two disjunct populations of Hudsonian godwits Limosa haemastica breeding at Churchill, Manitoba and Beluga River, Alaska. Only one population experienced a mismatch: godwits bred nearly one week after the onset of the invertebrate peak at Churchill because of asynchronous climatic change occurring throughout their annual cycle. However, chicks were not uniformly affected by the mismatch — growth rates and survival of young chicks were not correlated with invertebrate abundance, but older chicks tended to suffer lower survival rates on days of low invertebrate abundance. Ecological mismatches thus resulted in a complex array of consequences, but nonetheless contributed to reductions in chick survival. In contrast, godwits at Beluga River hatched their chicks just before the invertebrate peak, such that the period of highest energetic need coincided with the period of highest invertebrate abundance. As a result, growth rates and survival of godwit chicks were unaffected by invertebrate abundance. Godwits at Beluga River were able to properly time their reproduction because of predictable rates of climatic change and strong selection imposed by high predation on late‐hatched chicks. Taken together, our results suggest that population‐specific, local‐scale selection pressures play a critical role in determining the degree and severity of ecological mismatches. The potential for global climate change to induce species‐level population declines may therefore be mediated by the spatial variation in the selection pressures acting across a species' range.